Optimizing Goat Feed Production: The Role of Chopper Machine Technology - Damayanti, Retno; Malin Sutan, Sandra; Hendrawan, Yusuf; Firmanda Al Riza, Dimas; Bagus Hermanto, Mochamad; Setiawan, Dwi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2025)
The application of grass chopper technology in the livestock sector plays an important role in increasing the efficiency of feed provision, particularly for goat farms. This study aims to analyze the effectiveness of the use of grass chopper machines in accelerating the availability of feed and its impact on the productivity of goat farms. The methods used included observation and direct interviews with farmers who applied this technology. The results of the study showed that the grass chopper machine was able to shorten feed preparation time by up to 50% so that farmers could provide sufficient and quality feed in a shorter time. The machine capacity is 200 kg/h, with an average chopped size of approximately 3-4 cm. Consistent chopping can increase feed digestibility, which contributes to increased body weight and livestock health.